2006
DOI: 10.1097/01.cmr.0000215029.62199.4c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of angiogenin on the growth of A375 human melanoma cells and the expression of basic fibroblast growth factor

Abstract: Angiogenin was isolated as a tumor angiogenic factor solely on the basis of its angiogenic activity. Its expression is essential for melanoma progression and metastasis. Many studies have mainly focused on how it induces angiogenesis, which allows further melanoma growth and metastasis. Here, we investigated the effects of angiogenin on melanoma cell growth and studied its influence on the expression and function of the basic fibroblast growth factor. We transfected the angiogenin gene in the sense and antisen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Kishimoto et al reported that the expression of bFGF increased in angiogenin antisense transfected HeLa cells (24). Song et al found that the angiogenin sense transfected A375 actually expressed a lower amount of bFGF, and the angiogenin antisense transfectants expressed a higher amount of bFGF than the control cells (25). It seems that bFGF and angiogenin could interact, although the mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kishimoto et al reported that the expression of bFGF increased in angiogenin antisense transfected HeLa cells (24). Song et al found that the angiogenin sense transfected A375 actually expressed a lower amount of bFGF, and the angiogenin antisense transfectants expressed a higher amount of bFGF than the control cells (25). It seems that bFGF and angiogenin could interact, although the mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Kishimoto et al have observed that angiogenin antisense HeLa transfectants and tumors in athymic mice actually expressed a higher amount of bFGF than the control cells and tumors in athymic mice (24). Song et al demonstrated that the angiogenin sense transfectants actually expressed a lower amount of bFGF, and the angiogenin antisense transfectants expressed a higher amount of bFGF than A375 cells (25). To further understand the biological role of angiogenin and bFGF, we investigated the influence of bFGF on angiogenin gene expression and angiogenin secretion in HeLa cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Ang is up-regulated in numerous tumors (Tello-Montoliu et al, 2006), and also found in normal cells (Fernández-Santiago et al, 2009). Isolation of Ang from normal human plasma demonstrates that Ang is not a tumorspecific product (Song et al, 2006), but may also have some other biological activities in addition to angiogenesis.…”
Section: Introductionmentioning
confidence: 98%
“…In melanoma cell line, basic fibroblast growth factor cannot induce proliferation in the absence of Angiogenin (Song et al 2006). Knock down studies in HeLa cells showed notable inhibition of proliferation, and in prostate adenocarcinoma cells, its knock down caused inhibition of rRNA transcription, cell proliferation, and xenograft growth in mice (Tsuji et al 2005;Yoshioka et al 2006).…”
Section: I) Angiogeninmentioning
confidence: 99%